2015
DOI: 10.1093/jb/mvv067
|View full text |Cite
|
Sign up to set email alerts
|

Functional implication of archaeal homologues of human RNase P protein pair Pop5 and Rpp30

Abstract: PhoPop5 and PhoRpp30 in the hyperthermophilic archaeon Pyrococcus horikoshii, homologues of human ribonuclease P (RNase P) proteins hPop5 and Rpp30, respectively, fold into a heterotetramer [PhoRpp 30(PhoPop5) 2 PhoRpp30], which plays a crucial role in the activation of RNase P RNA (PhopRNA). Here, we examined the functional implication of PhoPop5 and PhoRpp30 in the tetramer. Surface plasmon resonance (SPR) analysis revealed that the tetramer strongly interacts with an oligonucleotide including the nucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…It is known that the binding of L7Ae family proteins to their cognate RNAs forms additional protein binding sites on RNAs, thereby enabling subsequent assembly of RNPs [23,24]. Since P16 in SL16, to which the PhoPop5-PhoRpp30 complex binds, is in close proximity to the K-turn in SL16 [25], it is likely that the PhoRpp38 binding to the K-turn in SL16 leads to a specific conformation of the 3-nucleotide bulge structure, the K-turn thus optimizing a double-stranded structure In this docking model, three PhoRpp38 were readily able to locate on K-turns in SL12 and SL16 without steric hindrance of the PhoPop5-PhoRpp30 complex which bridges P3 and P16 helices in PhopRNA.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the binding of L7Ae family proteins to their cognate RNAs forms additional protein binding sites on RNAs, thereby enabling subsequent assembly of RNPs [23,24]. Since P16 in SL16, to which the PhoPop5-PhoRpp30 complex binds, is in close proximity to the K-turn in SL16 [25], it is likely that the PhoRpp38 binding to the K-turn in SL16 leads to a specific conformation of the 3-nucleotide bulge structure, the K-turn thus optimizing a double-stranded structure In this docking model, three PhoRpp38 were readily able to locate on K-turns in SL12 and SL16 without steric hindrance of the PhoPop5-PhoRpp30 complex which bridges P3 and P16 helices in PhopRNA.…”
Section: Discussionmentioning
confidence: 99%
“…SPR studies of PhoPop5 mutants further revealed that the C-terminal helix (α4) in PhoPop5 function as a molecular recognition element for SL3. 62) These results, together with available data, allow us to generate a mechanistic model for the PhopRNA activation by PhoPop5 and PhoRpp30, as shown in Fig. 4(C).…”
Section: Iiii Structure and Function Of The Phopop5-phorpp30 Complexmentioning
confidence: 92%
“…58) Moreover, surface plasmon resonance (SPR) analysis revealed that the tetramer strongly interacts with an oligonucleotide including the nucleotide sequence of SL3 in PhopRNA. 62) In contrast, PhoPop5 had markedly reduced affinity to SL3, and PhoRpp30 had little affinity to SL3. SPR studies of PhoPop5 mutants further revealed that the C-terminal helix (α4) in PhoPop5 function as a molecular recognition element for SL3.…”
Section: Iiii Structure and Function Of The Phopop5-phorpp30 Complexmentioning
confidence: 93%
See 1 more Smart Citation
“…In archaea, bacteria, and yeast, RPP30/RPP30 paired with Pop5/Pop5, may be functionally reconstituted with the phylogenetically-conserved core catalytic domain (C domain) of the RNA subunit to promote the assembly of RNase P providing substrate RNA binding sites and activating the RNA subunit (probably by RNA annealing and strand displacement ( 41 ) and stabilize ionic interactions with the RNA subunit or the substrate pre-tRNA at a relatively lower salt concentration ( 1 , 22 , 42 44 ). In the hyperthermophilic archaeon Pyrococcushorikoshii , PhoRPP30 is homologous to human RPP30 and acts as a molecular chaperone of PhoPop5, which recognizes the stem-loop containing the P3 helix in PhopRNA ( 45 ). RPP30-Pop5 is a tight heterotetrameric complex that increases the affinity of the holoenzyme for Mg 2+ and protects the RNase P M1 RNA’s C domain from RNase T1 cleavage, especially near conserved nucleotides of RNase P in archaea whose RNase P protein is homologous to eukaryotic counterparts ( 36 , 46 48 ).…”
Section: Main Functions Of Rpp30mentioning
confidence: 99%